2014
DOI: 10.1139/cjfr-2013-0201
|View full text |Cite
|
Sign up to set email alerts
|

Wood density of Norway spruce in uneven-aged stands

Abstract: This study focused on wood density and annual ring width in Norway spruce (Picea abies (L.) Karst.) grown in uneven-aged stands (UAS). In total, 96 trees were harvested from five UAS that had been managed by single-tree selection for decades. A data set of 27 trees from even-aged stands (EAS) was used for comparison. In the UAS trees, high density and narrow annual rings were found in the juvenile wood near the pith. Thereafter, wood density rapidly decreased until the 20th annual ring, followed by an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…For instance for spruce an increase in tree-ring width was found to decrease wood density (Mäkinen et al 2007;Piispanen et al 2014;Franceschini et al 2010), while for oak Guilley et al (2004) found that an increase in tree-ring width results in an increase in wood density.…”
Section: Introductionmentioning
confidence: 99%
“…For instance for spruce an increase in tree-ring width was found to decrease wood density (Mäkinen et al 2007;Piispanen et al 2014;Franceschini et al 2010), while for oak Guilley et al (2004) found that an increase in tree-ring width results in an increase in wood density.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns also exist about lower log quality for trees that grow in highly variable conditions throughout their lives. This variability can exhibit itself in somewhat adverse branching patterns, including large branch sizes and higher variation in juvenile wood, wood density, and growth rings (Schütz 1999b;Macdonald et al 2010;Piispanen et al 2014).…”
Section: Economic Challengesmentioning
confidence: 99%
“…While these conclusions were derived from natural regeneration after clear felling, they are potentially applicable to natural regeneration in gaps or under a canopy. Indeed, Piisapanen et al [78] reported that a reduced juvenile core with higher wood density was characteristic of natural regeneration of Norway spruce (Picea abies (L.) Karst.) in both even-aged and uneven-aged stands.…”
Section: Timber Qualitymentioning
confidence: 99%